Single mutations convert an outward K(+) channel into an inward K(+) channel - Li, Legong (National Academy of Sciences, 2008)
Shaker-type K(+) channels in plants display distinct voltage-sensing properties despite sharing sequence and structural similarity. For example, an Arabidopsis K(+) channel (SKOR) and a tomato K(+) channel (LKT1) share high amino acid sequence similarity and identical domain structures; however, SKOR conducts outward K(+) current and is activated by positive membrane potentials (depolarization), whereas LKT1 conducts inward current and is activated by negative membrane potentials (hyperpolarization). The structural basis for the “opposite” voltage-sensing properties of SKOR and LKT1 remains unknown. Using a screening procedure combined with random mutagenesis, we identified in the SKOR channel single amino acid mutations that converted an outward-conducting channel into an inward-conducting channel. Further domain-swapping and random mutagenesis produced similar results, suggesting functional interactions between several regions of SKOR protein that lead to specific voltage-sensing properties. Dramatic changes in rectifying properties can be caused by single amino acid mutations, providing evidence that the inward and outward channels in the Shaker family from plants may derive from the same ancestor.